Relation between maternal vitamin D level and in vitro-fertilization laboratory outcome in normal responding patients 35 years old or less - Bahgat, Nagwan Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Vitamin D relation to pregnancy outcome have been extensively studied and proved, but the relation between the vitamin D and fertility and fertility treatment especially in vitro-fertilization still a matter of debate. Methods: A retrospective cohort study in large IVF center in Abu Dhabi, UAE involved young normal responding patients aged 35 years old or less attending the clinic for IVF treatment. Patient were divided in to three groups according to the serum level of vitamin D. the IVF laboratory outcome was calculated and compared in the three groups. Results: We found that the prevalence of vitamin D in patients seeking fertility treatment especially IVF was significantly high. But on the other hand, and after analysing the results of the cycles laboratory out come in the three groups, we found that no significant difference that could be attributed to maternal level of vitamin D. Conclusions: The prevalence of vitamin D deficiency and insufficiency in infertile patients is significantly high but no significant effect of vitamin D deficiency on the IVF laboratory outcome.